2008
DOI: 10.1021/ja077831q
|View full text |Cite
|
Sign up to set email alerts
|

A Doorway State Leads to Photostability or Triplet Photodamage in Thymine DNA

Abstract: Ultraviolet irradiation of DNA produces electronic excited states that predominantly eliminate the excitation energy by returning to the ground state (photostability) or following minor pathways into mutagenic photoproducts (photodamage). The cyclobutane pyrimidine dimer (CPD) formed from photodimerization of thymines in DNA is the most common form of photodamage. The underlying molecular processes governing photostability and photodamage of thymine-constituted DNA remain unclear. Here, a combined femtosecond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
238
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(252 citation statements)
references
References 109 publications
10
238
1
3
Order By: Relevance
“…18 In the other case the decay was ascribed to the quenching of triplet states eventually leading to the formation of cyclobutane pyrimidine dimer (CPD) lesions. 14 Neither of the studies reported direct evidence for the interpretations due to the lack of conclusive spectral signatures in the UV and visible spectral range monitored in these experiments. In this study, we applied time resolved IR spectroscopy (TRIR) to reinvestigate the picosecond dynamics in the allthymine single strand (dT) 18 .…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…18 In the other case the decay was ascribed to the quenching of triplet states eventually leading to the formation of cyclobutane pyrimidine dimer (CPD) lesions. 14 Neither of the studies reported direct evidence for the interpretations due to the lack of conclusive spectral signatures in the UV and visible spectral range monitored in these experiments. In this study, we applied time resolved IR spectroscopy (TRIR) to reinvestigate the picosecond dynamics in the allthymine single strand (dT) 18 .…”
mentioning
confidence: 81%
“…Reaction dynamics on the 100 ps time scale have been observed in two independent studies on (dT) 18 and (dT) 20 . 14,18 In one case the decay was tentatively assigned to a singlet np* state. 18 In the other case the decay was ascribed to the quenching of triplet states eventually leading to the formation of cyclobutane pyrimidine dimer (CPD) lesions.…”
mentioning
confidence: 99%
“…Therefore, the nature of hydrogen bond in solution is of particular interest and has been investigated extensively by various experimental and theoretical methods, since solute-solvent interactions play a fundamental role in molecular nonequilibrium processes in liquids [11][12][13][14][15][16][17][18][19][20][21][22][23]. However, little is known about electronic excited-state hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…This photolesion, which can take place in both the singlet and triplet manifolds, has been extensively investigated spectroscopically [2][3][4][5][6][7] and computationally [8][9][10][11][12][13][14][15]. The triplet pathway is a much slower process [7] and exhibits a smaller yield [6,16] than the singlet mechanism due to inefficient intersystem crossing. As a consequence, this pathway yields very weak spectroscopic signals that preclude unambiguous statements regarding the mechanism [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The triplet pathway is a much slower process [7] and exhibits a smaller yield [6,16] than the singlet mechanism due to inefficient intersystem crossing. As a consequence, this pathway yields very weak spectroscopic signals that preclude unambiguous statements regarding the mechanism [5][6][7]. In order to enhance the triplet signals, photosensitization is commonly used, increasing the ThiT dimerization yield [5,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%